Characterization and Photoprotector Activity of Endophytic Fungal Pigments from Coastal Plant Sarang Semut (Hydnophytum formicarum) - Mada Triandala Sibero; Kustiariyah Tarman; Novriyandi Hanif (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
Endophytic fungus RS3 isolated from coastal plant sarang semut (Hydnophytum formicarum) produced extracellular black pigment. The aims of this research were to obtain the pigment, to characterize and to determine the photoprotector activity. This research was conducted into several steps, that were determination of the best precipitating agent, characterization using instrument and solubility analysis, and analysis of Sun Protection Factor (SPF). Results showed the pigment was precipitated using acid solvent with pH ≤ 2.5. Functional groups of pigment were hydroxyl, aromatic ring, phenol and amine. According to its characteristics, black pigment produced by RS3 isolate was proposed as melanin. The photoprotector analysis showed the SPF value was 11.33.